(untitled) - Bainbridge, David A. (Washington, DC, 2007)
The book discusses the ecology of desert plants, explores the causes of desertification and land abuse, and outlines the processes and procedures needed to evaluate, plan, implement, and monitor desert restoration projects. It sets forth economical and practical field-tested solutions for understanding site characteristics, selecting and growing plants, and ensuring that they survive with a minimal amount of water and care. Each chapter represents a guide to a critical topic for environmental restoration; extensive photographs, diagrams and drawings give detailed information for immediate application, and additional resources are included in appendixes.
Keywords: Deserts,Sa mạc